Malawi Public Expenditure Review - World Bank (Washington, DC, 2014)
This public expenditure review (PER 2013) is prepared in response to a request by the Government of Malawi (GOM). It is aligned with the fifth country assistance strategy (CAS) FY2013-FY16. The PER offers policies to improve public expenditure efficiency defined in the context of Malawi as delivering similar or improved level and quality of government services with constrained overall resource envelope as described in the new GOM fiscal framework. The PER has four main objectives. First, it supports the government to enhance the quality and efficiency of public financial management and provide inputs to the preparation of its budget. Second, it complements the on-going public finance and economic management (PFEM) reforms. Third, it provides development partners in Malawi with analytical inputs into their operations. Fourth, the PER is expected to become a crucial component of the implementation of the fiscal framework, underpinning the new extended credit facility (ECF) agreed with the International Monetary Fund (IMF) in July 2012. The PER 2013 consists of seven chapters. The first two chapters focus on the overall macro-fiscal framework, planning, and budgeting processes. Chapters 3 to 7 analyze the allocative, technical efficiency, and equity of sectoral public expenditures in agriculture, transport, education, health, and social protection respectively.